As transfigurações do mito de Ariadne e Dionísio em Hilda Hilst - Alves, Luana Franciele Fernandes (2020)
The arts search in the myths inspiration to (re)discuss contemporary themes, as we can observe in the poetic set that composes the book Jubilo, Memory, Novitiate of Passion (1974), by Hilda Hilst and which are the object of study of this research, in an attempt to describe the transfiguration in “Discontinuous and remote Ode to flute and oboe. From Ariana to Dionysus”. An exploratory research was carried out in bibliographies, journals and websites, as well as research in the documents of the Hilda Hilst Institute, located in Campinas - SP, and document analysis at the Unicamp's "Alexandre Eulálio" Cultural Documentation Center. It can be seen that the transfiguration is present in all the researched work, either in the figure of the God who becomes human before the beloved, or in Ariadne's transposition of mythology to Ariana by Hilda Hilst. It is noticed that there is a heterosexual erotic relationship and alterity would be related, then, to a desire for the other sex, a desire, however, that does not seem to find a solution. It is in this erotic game of constant postponement of enjoyment that the other is constructed in the poems that make up the object of study.